Purification and some properties of an alkaline protease from rat skeletal muscle - Bosch, Benjamin (Division of Medical Biochemistry and Structural Biology, 2018)
Various alkaline proteases derived from skeletal muscle have been described by a number of researchers and have been purified to varying degrees. Such alkaline proteases may play an important role in the metabolism of myofibrillar and other muscle proteins and as such deserve to be fully characterised. In this study, a major myofibrillar alkaline protease was purified from rat skeletal muscle. The enzyme degraded both denatured casein and azocasein and had a pH optimum of 9,0. The molecular mass was 32 250 ± 650. The presence of a second, minor alkaline protease was demonstrated using three different separation techniques as well as by inhibitor studies. The major protease was insensitive to inhibition by pepstatin and leupeptin, whilst 90 % of the activity was expressed in the presence of 2 mM EGTA. A moderate degree of inhibition was observed in the presence of soybean trypsin inhibitor and the protease was markedly sensitive to chymostatin. A similar alkaline protease was partially purified from rat cardiac muscle using the same purification procedure. Incubation of washed myofibrils in the presence of sodium pyrophosphate released a factor into the supernatant, the removal of which facilitated the separation of myofibrillar alkaline protease from the myofibrils. The factor appeared to be necessary for binding of the alkaline protease to the myofibrillar proteins but its removal did not disrupt the binding of proteolytic activity already attached to the myofibrillar proteins. An inhibitor of myofibrillar alkaline protease was demonstrated which is, in principle, capable of playing an important regulatory role in controlling the activity of these enzymes and thereby of myofibrillar protein catabolism.